TGFíŸ3 / SfaN1 gene variant and the risk factor of nonsyndromic cleft palate only among Indonesian patients - Nasroen, S. L.; Tajrin, A.; Fauziah, P. N.; Maskoen, A. M.; Soemantri, E. S. S.; Soedjana, H.; Hilmanto, D. (Cellular and Molecular Biology, 2017)
Non-syndromic cleft palate only (NS CPO) is one of the most common congenital malformations that affect between 1 in 1000 - 2500 live births worldwide. The etiopathogenesis of clefts including NS CPO has been widely studied but is still poorly understood. NS CPO is considered to be a genetically complex, multifactorial disease. Based on several studies, mutations of TGFÎ²3 gene emerged as the strong candidate gene associated with NS CPO. The purpose of this study was to analyze the relationship between the TGFÎ²3 / SfaN1 gene variant and the risk of NS CPO in Indonesian patients. This study was case control design using samples from 31 NS CPO subjects and 35 control subjects. DNA was extracted from venous blood and the segment of TGFÎ²3 gene/ SfaN1 were amplified by using polymerase chain reaction (PCR) technique, then digestion products by SfaN1 restriction enzyme which can detect locus of gene variant / polymorphism from restriction fragment length polymorphisms (RFLP) method were evaluated. The results indicated that the gene variant as substitution of base G into A was identified in TGFÎ²3 gene and the frequency of heterozygous mutant GA genotype was 63,6% in NS CPO subjects and 36,4% in control subjects. The frequency of heterozygous mutant GA genotype was associated with increased risk of NS CPO (odds ratio (OR) = 2,260, 95% CI = 0,592 - 8,625). In conclusion, TGFÎ²3 gene / SfaN1 polymorphism can be considered as the risk factor associated with NS CPO in Indonesian patients.